2022
DOI: 10.1111/jdi.13957
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene panel analysis of Japanese patients with maturity‐onset diabetes of the young‐like diabetes mellitus: Roles of inactivating variants in the ABCC8 and insulin resistance genes

Abstract: Aims/Introduction: To investigate the genetic background of Japanese patients with suspected maturity-onset diabetes of the young (MODY). Materials and Methods: On 340 proband patients referred from across Japan, genomic variants were analyzed using a targeted multigene panel analysis combined with the multiplex ligation probe amplification (MLPA) analysis, mitochondrial m.3243A > G analysis and methylation-specific polymerase chain reaction of the imprinted 6q24 locus. Pathogenic/likely pathogenic variants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…In the present study, which was conducted on 55 non-obese children clinically diagnosed with type 2 diabetes, IGF, and IGT, 21 were identified as having MODY by genetic testing. This mutation identification rate (38.2%) was similar to that reported in previous studies conducted on Japanese children ( 22 , 23 ). Urine glucose screening in schools can detect not only a large number of children with type 2 diabetes but also MODY before the progression of diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, which was conducted on 55 non-obese children clinically diagnosed with type 2 diabetes, IGF, and IGT, 21 were identified as having MODY by genetic testing. This mutation identification rate (38.2%) was similar to that reported in previous studies conducted on Japanese children ( 22 , 23 ). Urine glucose screening in schools can detect not only a large number of children with type 2 diabetes but also MODY before the progression of diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…The most common type of MODY is reported to be MODY3, as evidenced by its detection in Europe, North America, and Asia (24,25). In contrast, Yorifuji et al (22,23) reported that the most common type of MODY among Japanese children was MODY2, followed by MODY3. The present study also showed that the most common type was MODY2 with the same frequency as MODY3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations